A esmola e a rede de proteção : um estudo de instituições assistenciais para as pessoas que vivem nas ruas - Melo, Natália Maximo e (2016)
Innumerous City Halls all over Brazil promote periodic campaigns using slogans such as: “Do not spare money: give citizenship and future”, or “Do not spare money. Refer to Assistance services”. Based on these assumptions, we intend to investigate the strategies followed by São Carlos (SP) government in order to manage this population and to keep these people under institutional control. São Carlos was one of the first non-metropolitan cities where homeless population issues were articulated to the establishment of Municipal-Level Public Policies. Having these aspects in mind, some research questions can emerge: Which is this population that is considered as a target by the government? What is the Institutions’ role in the management of homeless people? Methodologically, we observe some practices promoted by the institutions which manage this population, analyzing them through the theories created by Das and Poole in their work State and its Margins: comparative ethnographies (2008). The margins, in our study, cover, thus, Governmental and Non-governmental Organizations; they also cover these organizations’ employees, target public and individuals who are helped by their assistance. Our research mainly investigates the Centro POP (a National Social Assistance Policy Unit administrated by the City Hall) as well as the Hostel (a philanthropic institution which supports and donates tickets to travellers) and the Religious Community (a volunteer work that assists homeless people). To develop this research, we collected in two newspapers from São Carlos dated from 2007 to 2013, as well as the Centro POP’s documentation. We interviewed several people who work at Centro POP and observed their routine as well. Our investigation also based its analysis on the verification of volunteer work promoted by a religious group on a City Center Square and on visits to Assistance Institutions, such as a Hostel and a Religious Community (House of Prayer), related to charity and shelter. We verify these data under Foucault’s (1992, 1999, 2006, 2008) perspectives. According to them, power permeates all kinds of relationships, shaping a microphysics which combines technology and power mechanisms to develop a population that may be managed, articulating some disciplines which, in turn, dominate individuals’ bodies and souls. The results show that a homeless population local Policy may be considered as a device, in which homeless people are connected to social representation, to institutional rules, to philanthropic and state institutions, their specialized professionals, according to a labyrinth of population management.